Novel Adaptive Method of Setting Parameters for Marsik Control Algorithm - Samuel Alexik (Communications - Scientific letters of the University of Zilina, 2003)
A novel method of Marsik algorithm improvement is described in the paper. The KappaZ parameter in Marsik algorithm representing a required rate of control error oscillations that influences the quality of control most can be changed adaptively to obtain a better process performance. In the original version of the algorithm a constant value of KappaZ = 0,5 is recommended by the author. Here, a concept how to improve control performance by adaptively changing KappaZ is described. An analysis of the parameter influence is made.